2016
DOI: 10.1016/j.dam.2015.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Generalized minor inequalities for the set covering polyhedron related to circulant matrices

Abstract: We study the set covering polyhedron related to circulant matrices. In particular, our goal is to characterize the first Chvátal closure of the usual fractional relaxation. We present a family of valid inequalities that generalizes the family of minor inequalities previously reported in the literature and includes new facet-defining inequalities. Furthermore, we propose a polynomial time separation algorithm for a particular subfamily of these inequalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…In the particular case when A = C k n , facet defining inequalities of Q * (C k n ) related to circulant minors were studied in [2,8,9,29,30].…”
Section: Preliminariesmentioning
confidence: 99%
“…In the particular case when A = C k n , facet defining inequalities of Q * (C k n ) related to circulant minors were studied in [2,8,9,29,30].…”
Section: Preliminariesmentioning
confidence: 99%
“…Circulant minors of C k n are known to induce valid (and in some cases facetdefining) inequalities for Q * (C k n ). The class of minor inequalities was introduced in [2] and was further studied and generalized in [4,13]. In [5] it was observed that a circulant minor C k n /N ≈ C k n also induces a row family inequality that either is equivalent to or enhances the corresponding minor inequality.…”
Section: Introductionmentioning
confidence: 99%
“…In [4] it was conjectured that (0, 1)-and (1, 2)-valued minor inequalities suffice to describe Q * (C k n ). This was disproved in [13], where a first example of a facet-defining (2, 3)-valued minor inequality is presented. Using similar ideas as for the case of P * (C k n ) in [8], in this paper we show that there are circulant matrices such that Q * (C k n ) has facet-defining minor related row family inequalities with two consecutive arbitrarily large coefficients.…”
Section: Introductionmentioning
confidence: 99%